The Role of Pulmonary Surfactants in the Treatment of Acute Respiratory Distress Syndrome in COVID-19 - Shengguang Wang; Zhen Li; Xinyu Wang; Shiming Zhang; Peng Gao; Zuorong Shi (Frontiers Media S.A., 2021)
Lung alveolar type-II (AT-II) cells produce pulmonary surfactant (PS), consisting of proteins and lipids. The lipids in PS are primarily responsible for reducing the air-fluid surface tension inside the alveoli of the lungs and to prevent atelectasis. The proteins are of two types: hydrophilic and hydrophobic. Hydrophilic surfactants are primarily responsible for opsonisation, thereby protecting the lungs from microbial and environmental contaminants. Hydrophobic surfactants are primarily responsible for respiratory function. Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) enters the lungs through ACE-2 receptors on lungs and replicates in AT-II cells leading to the etiology of Coronavirus disease - 2019 (COVID-19). The SARS-CoV-2 virus damages the AT-II cells and results in decreased production of PS. The clinical symptoms of acute respiratory distress syndrome (ARDS) in COVID-19 patients are like those of neonatal respiratory distress syndrome (NRDS). The PS treatment is first-line treatment option for NRDS and found to be well tolerated in ARDS patients with inconclusive efficacy. Over the past 70°years, a lot of research is underway to produce natural/synthetic PS and developing systems for delivering PS directly to the lungs, in addition to finding the association between PS levels and respiratory illnesses. In the present COVID-19 pandemic situation, the scientific community all over the world is searching for the effective therapeutic options to improve the clinical outcomes. With a strong scientific and evidence-based background on role of PS in lung homeostasis and infection, few clinical trials were initiated to evaluate the functions of PS in COVID-19. Here, we connect the data on PS with reference to pulmonary physiology and infection with its possible therapeutic benefit in COVID-19 patients.